Tourism and culture: reflection about its practice in afro communities of Latin America and the Caribbean - Calle Ruiz, Samanta Hilda (2019)
The discussion about the use of the cultural heritage in the tourist context in permanent and unfinished. ¡How the culture is show to others with socioeconomic, commercial or political goals? ¿Is the tourism a factor of non beneficial situation for the communities’ wellness? If the cultural heritage is what give sense of integration and the expression of the persons in their social environment with the purpose of generate their own wellness. So, the decision of choose a way correspond to themselves. Nevertheless, the inequality and the inequity are gaps that do not allow the common benefit.